Selenium status during pregnancy: Influential factors and effects on neuropsychological development among Spanish infants - Amorós, Rubén; Murcia, Mario; Ballester, Ferran; Broberg, Karin; Iñiguez, Carmen; Rebagliato, Marisa; Skröder, Helena; González, Llúcia; Lopez-Espinosa, Maria-Jose; Llop, Sabrina (The Science of the total environment, 2018)
Selenium (Se) has been positively associated with neurodevelopment in early life. However, its margin of safety is rather narrow, and few prospective studies have evaluated its potential neurotoxic effects at intermediate levels. We aimed to explore the association between maternal Se concentrations and child neuropsychological development, including the genetic effect modification of the Se metabolizing gene INMT. Study subjects were 650 mother-child pairs from the Spanish Childhood and Environment Project (INMA, 2003–2005). Infant neuropsychological development was assessed around 12months of age by the Bayley Scales of Infant Development. Sociodemographic and dietary characteristics were collected by questionnaire at the first and third trimester of gestation. Se was measured in serum samples at the first trimester. The mean serum Se concentration was 79.7 (standard deviation=7.9) μg/L. In multivariate analysis, nonsignificant inverse linear associations were found between Se concentrations and standardized mental and psychomotor development scores (β (95% CI)=−0.13 (−0.29, 0.03) and β (95% CI)=−0.08 (−0.24, 0.07), respectively). Generalized additive models indicated inverted U-shaped relationships between Se concentrations and both scales. Using segmented regression, the turning point for the associations was estimated at 86μg/L for both scales. The association between Se and neuropsychological development was inverted U-shaped for children with the AG+AA genotype for rs6970396 INMT but a descending curve was suggested for the GG genotype. Further studies would be necessary in order to disentangle the complex equilibrium between the toxicity and benefits of Se exposure during the prenatal period. [Display omitted] •Potential neurotoxic effects of selenium at intermediate levels are scarcely studied.•We examined the determinants of Se levels at the first trimester of gestation.•We explored the association between maternal Se and child neurodevelopment at 12months of age.•An inverted U-shaped relationship was found between maternal Se and child neurodevelopment.